OPTIMIZATION OF CARDIOPROTECTION IN YOUNG CHILDREN: EFFECTIVENESS OF THE MODIFIED DEL NIDO SOLUTION (Herald of the National Children's Medical Center, 2025)
To evaluate the effectiveness of a modified Del Nido solution with the addition of oxygenated autokrov in cardiac surgery in young children with congenital heart defects.
Keywords: cardioprotection; congenital heart defects; autoblood; pediatric cardiac surgery